TRENDS IN THE MODERNIZATION OF THE CRIMINAL LAW RESPONSE TO DRUG CRIME - Dziadkouski, Andrei (Administrative and Criminal Justice, 2019)
The paper deals with the problem of countering the illicit drug trafficking, psychotropic substances, their precursors and analogues in the Eurasian Economic Union countries. The authors, basing on the statistical data analysis, demonstrated an increase in the number of drug addicts; it is shown that drug addiction is a global problem nowadays. The constant   increase of registered criminal acts related to drugs and their cross-border nature make it necessary to develop cooperation in combating the illicit distribution of drugs, harmonizing and unifying legal norms in this area, especially within the framework of the Eurasian Economic Union. A comparative legal analysis of the criminal law governing liability for drug trafficking in the EAEU countries shows the diversity of legislative structures in the key elements of the crimes under consideration. The issues of personal non-medical use liability, the subject of crimes, the criminalization of individual acts related to drug trafficking, should be the subject of discussion on developing a unified approach of criminal law to counter the analyzed crimes in the EAEU countries.